IMPROVEMENT OF THERMAL STABILITY OF THE PLASTICIZED POLY(L-LACTIC ACID) PLLA BY RADIATION CROSSLINKING - TRAN , MINH QUYNH; TRAN , BANG DIEP; MOHAMMED IQBAL SHUEB; KAMARUDDIN BIN HASHIM (Nuclear Science and Technology, 2012)
Poly(lactic acid), PLLA was plasticized using low molecular weight polyethylene glycol, PEG 1000 in order to improve its toughness and thereby promoting the applications of PLLA based materials. Differential scanning calorimetry data showed that the presence of PEG was much reduced the glass transition temperature as well as melting point of PLLA. This reduction increased with the PEG content, but the PLLA blend with 5% PEG was chosen for preparation of the radiation-induced crosslinking samples. The cold crystallization of the crosslinked PLLA was much reduced and its melting point shifted to lower temperature with smaller area by irradiation. Typical crosslinked PLLA showed very low crystallinity and high heat stability as indicated by dynamic mechanical analysis.